PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN - Sundari Soekotjo (ESENSI: Jurnal Manajemen Bisnis, 2015)
The study aims to find out the effect of organizational culture, leadership behavior on the job satisfaction of the employee organization of PT Pembangunan Perumahan (Persero). A survey was conducted with a randomly selected sample of 98 employees. With all the variables put into a correlation matrix, the data was then analyzed with the path technique. The result showed that: (1) organizational culture had effect on the employee’s job satisfaction; (2) leadership behavior had effect on the employee’s job satisfaction; the results suggest that organizational culture, leadership behavior are important determinants of the job satisfaction.